“Solid state chemistry and its applications” de Anthony R. West - Ortega San Martín, Luis (Pontificia Universidad Católica del Perú, 2014)
Short review of the most important and interesting sections of the textbook in solid state chemistry “Solid state chemistry and its applications” written by the well-known chemist Anthony R. West. John Wiley and Sons, Ltd., Chichester, 2014. 556 pages. ISBN: 978-1-119-94294-8

Repaso de algunos de los aspectos más destacados e interesantes de la segunda edición del libro de texto de química del estado sólido escrito por el conocido químico Anthony R. West titulado “Solid state chemistry and its applications”. John Wiley and Sons, Ltd., Chichester, 2014. 556 páginas. ISBN: 978-1-119-94294-8
“Solid state chemistry and its applications” by Anthony R. West
Keywords: Química; https://purl.org/pe-repo/ocde/ford#1.04.00